2004
DOI: 10.1038/modpathol.3800070
|View full text |Cite
|
Sign up to set email alerts
|

Sequential clinical and histopathological changes in collagenous and lymphocytic colitis over time

Abstract: We conducted this retrospective study to evaluate the relationship between symptoms, histological findings, and treatment of collagenous (CC) and lymphocytic colitis (LC). We identified 19 CC and 12 LC patients having multiple colonoscopic procedures with colonic biopsies during their course of illness. A detailed histological review of all biopsies was performed. Clinical history, including symptoms and medications, was obtained in 25 of the 31 patients and was correlated with their histological findings. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 10 publications
4
28
1
1
Order By: Relevance
“…6,21 We are aware that changes suggestive of idiopathic inflammatory bowel disease, including crypt architecture distortion, acute crypt inflammation, and Paneth cell metaplasia have been described as part of the histologic spectrum of lymphocytic colitis in the adult population. 22,23 However, all of the patients with these changes, in addition to colonic intraepithelial lymphocytosis, proved to have idiopathic inflammatory bowel disease within our follow-up period.…”
Section: Discussionmentioning
confidence: 74%
“…6,21 We are aware that changes suggestive of idiopathic inflammatory bowel disease, including crypt architecture distortion, acute crypt inflammation, and Paneth cell metaplasia have been described as part of the histologic spectrum of lymphocytic colitis in the adult population. 22,23 However, all of the patients with these changes, in addition to colonic intraepithelial lymphocytosis, proved to have idiopathic inflammatory bowel disease within our follow-up period.…”
Section: Discussionmentioning
confidence: 74%
“…Ayata et al, 17 in a review of 79 LC and 71 CC cases, found no evidence of basal lymphoid aggregates, but others suggest that lymphoid follicles and aggregates are an early event in the course of CC and LC. 18 Although it would be interesting to hypothesize that our observation could be better placed in the MC spectrum, our patients differ clinically by (1) slightly male predominance; (2) a younger mean age; (3) and lack of association with autoimmune disease and nonsteroidal anti-inflammatory drug intake. In any case, this should be placed in the limiting context of the relative small sample size of this study.…”
Section: Commentmentioning
confidence: 99%
“…The following histologic parameters were examined according to previous studies [14][15][16][17][18][19][20][21][22][23] :…”
Section: Histology Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unclear whether local expansion or infiltration is responsible for an increase in T cells [71,139]. Absent correlation between the severity of the clinical symptoms and IEL numbers or thickness of the collagen layer as characteristic features of the two entities points to a dominance of the inflammatory infiltrates in the mucosal lamina propria [140]. The LPL composition strongly depends on the disease state and the exact origin of the samples [141], which might help to explain differences in the T-cell compartment found in independent surveys.…”
Section: Microscopic Colitismentioning
confidence: 99%